A population-based cytogenetic study of adults with acute lymphoblastic leukemia - Moorman, Anthony V.; Chilton, Lucy; Wilkinson, Jennifer; Ensor, Hannah M.; Bown, Nick; Proctor, Stephen J. (Blood, 2010)
Chromosomal abnormalities are increasingly used to risk stratify adults with acute lymphoblastic leukemia. Published data describing the age-specific incidence of chromosomal abnormalities and their prognostic relevance are largely derived from clinical trials. Trials frequently have age restrictions and low recruitment rates. Thus we investigated these factors in a population-based cohort of 349 patients diagnosed during the course of 19 years in the northern part of England. The incidence of most chromosomal abnormalities varied significantly with age. The incidence of t(9;22)(q34;q11) increased in each successive decade, up to 24% among 40- to 49-year-old subjects. Thereafter the incidence reached a plateau. t(4;11)(q21;q23) and t(1;19)(q23;p13) were a rare occurrence among patients older than 60 years of age. In contrast, the frequency of t(8;14)(q24;q32) and t(14;18)(q32;q21) increased with age. High hyperdiploidy occurred in 13% of patients younger than 20 years of age but in only 5% of older patients. The incidence of low hypodiploidy/near-triploidy and complex karyotype increased with age from 4% (15-29 years) to 16% (≥ 60 years). Overall survival varied significantly by age and cytogenetics. Older patients and those with t(9;22), t(4;11), low hypodiploidy/near-triploidy, or complex karyotype had a significantly inferior outcome. These population-based results demonstrate the cytogenetic heterogeneity of adult acute lymphoblastic leukemia. These data will inform the delivery of routine clinical services and the design of new age-focused clinical trials.